VERTICAL FLOW OF BT GENES IN TRANSGENIC COTTON (Gossypium hirsutum L.) - S. Ramzan; Mahmood-ur-Rahman1; T. Shaheen; K. Hussain; M. Qasim; M. Asif; S. A. Bukhari (Journal of Animal and Plant Sciences, 2014)
Vertical gene flow is a major ecological concern where transgenic crops are under cultivation. Rate of vertical gene flow is helpful to determine genetic contamination of Bt and non-Bt cultivars. Vertical gene flow was determined by analyzing the DNA isolated from leaf samples. The DNA was amplified by PCR using gene specific primers for various Bt genes, e.g. MON-531 event, cry1Ac and cry2A genes. Total 316 samples including Bt (76 samples) and non-Bt (240 samples) cotton were analyzed. Bt cotton samples, showed 22%, 15% and 9% gene flow from non Bt cotton for MON531 event, cry1Ac and cry2A respectively. Non-Bt cotton resulted in 20%, 10% and 10% gene flow from Bt cotton for MON531 event, cry1Ac and cry2A respectively. The results clearly showed that MON531 event has major share in vertical gene flow in transgenic cotton in Pakistan. Our results indicated the current position of genetic contamination due to transgenic cotton in Pakistan. The percentage of gene flow will increase every passing year. So, here we recommend to cultivate Bt cotton according to the recommendations of National Bisafety Committee (NBC) and use of proper measures to control vertical gene flow.
Keywords: Bt cotton; cry1Ac gene; cry2A gene; Genetic contamination; MON531 event; Vertical gene flow